Magmatic Unrest at Long Valley Caldera, California, 1980-1990 - Bailey, Roy; Hill, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary On May 25, 1980,there sort town of Mammoth Lakes. California, was shaken by a remarkable 48-hour-long earthquake sequence that included four M=6, two M=5 and 300 M=3 quakes. The nature of the precursory seismicity plus the unusual character of the May 25-27 sequence itself suggested that it was not typical of tectonic earthquakes in the region. Discovery of 25 cm of domical uplift centred on the resurgent dome within LongValley caldera strongly implied that this activity was accompanied, if not caused, by influx of magma into the Long Valley magma chamber.